Determination of photocatalytic activity for the system: CdS chemical bath deposited thin films coated with TiO2 NPs - Carrillo, Amanda (2021)
At this research, it is proof the degradation of methylene blue colorant, as photocatalytic activity, which result from the interaction between a CdS thin film surface, coated by TiO2 NPs, and the molecules of an aqueous solution of methylene blue colorant. This heterogeneous device, TiO2 NPs/CdS thin film/Glass substrate, pump by solar radiation; can be used to wastewater treatment. CdS thin films, are deposited by chemical bath deposition, while the TiO2 nanoparticles (Nps) were obtained by a microwave-assisted solgel process method and deposited on CdS layer by spin coating technique. The main syntheses used techniques for these materials, are parts of the soft chemistry. The optical characterization of, TiO2 NPs/CdS thin films/Glass substrate, was evaluated by UV-vis spectroscopy, and the calculated band gap for the films was 2.8 eV. Agglomerations of TiO2 nanoparticles were observed on the homogeneous surface of polycrystalline hexagonal structure of the CdS thin films. The degradation of methylene blue colorant is carry out by three replicates of TiO2/NPs/CdS thin films/Glass substrate, exposed to sunlight for 60 minutes, resulting in a degradation of 43%. (Received